Carbon Reserve Potential, Carbon Dioxide Absorption Capacity, and Oxygen Release in The Conservation Forest of Kamojang, West Java - Maulana Abdul Ghani, Dadang; Fahmi Solihat, Raizal; Wilujeng, Sri (Greenation International Journal of Engineering Science, 2023)
This research aims to identify and measure the carbon reserve potential, carbon dioxide absorption capacity, and oxygen release of tree vegetation in the conservation forest area of Kamojang, West Java. The research method includes field data collection by measuring tree biomass and specific gravity analysis, using systematic sampling techniques to determine research plots. The results of the study indicate that the Cikaro and Cibeunying blocks have a potential carbon reserve of approximately 202,577 tons, a karbon dioxide absorption capacity of around 742,781 tons, and an oxygen release of about 540,132 tons. Tree species such as Pinus (Pinus merkusii), Kibeureum (Dystilium stellare), Manglid (Maglietia glauca), Puspa (Schima wallichii), and Ki Badak (Fagraea fragrans) contribute the most to the total carbon amount. This research provides essential information for the management of the Kamojang conservation forest area in forest management policies as a crucial carbon reserve source for climate change mitigation.